Cryptophthalmos and Bilateral Renal Agenesis with Cleft Lip and Palate: Fraser Syndrome: Case Report - Pabuçcu, Emre; Kahraman, Korhan; Özkavukçu, Esra; Karabulut, Yasemin; Koç, Acar (Gynecology Obstetrics & Reproductive Medicine, 2012)
Fraser syndrome is a rare autosomal recessive disorder consisting of multiple anomalies including variable expression of cryptophthalmos, syndactyly, abnormal genitalia, malformations of the nose, ear and larynx, renal agenesis, oro-facial clefts, skeletal defects, umbilical hernia and mental retardation. Antenatally detected multiple congenital fetal anomalies during 22nd week of gestation is reported in this paper. Fraser Syndrome was diagnosed according to major and minor criteria. Early antenatal detection is mandatory and clinician should be awere of the high recurrence rates of this syndrome among siblings threatening subsequent pregnancies and should inform affected families.